MEKANISME PENERBITAN AKTA PEMISAHAN RUMAH SUSUN SEBAGAI ALAS HAK LAHIRNYA SHM SARUSUN/SKBG SARUSUN BERIKUT PERALIHAN DAN PEMBEBANANNYA - DESY EKA WIDYANTARI (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2012)
Deed of High-Rise Separation is an important stage in the development and ownership ofhigh-rise because deed of separation is proof of high-rise separation upon high-rise units, mutualparts, mutual objects and mutual land with clear report in the form of drawings, descriptions andboundaries in vertical and horizontal directions which containing proportional comparison value.Proportional comparison value is very important for the owner of high-rise unit because itrepresents the owner’s rights and obligations on ownership, maintenance and management ofsuch high-rise. Proportional comparison value is a number that indicates the ratio high-rise unittowards the rights over mutual parts, mutual objects and mutual land, calculated based on totalarea and value of the concerned high-rise unit towards the building total area or the high-riseoverall value at the first time the developer calculates its overall development cost to determineits selling price. In relation to the issue of deed of separation, some problems raised as follow;firstly, its legal consequences if there is changes on building plan in further stage during thehigh-rise development which results in changes on proportional comparison value of the Deed ofHigh-Rise Separation, and secondly, whether strata unit and Strata title / Building title can beused as credit security and how is the implementation of partial revocation mortgage in high-riseconstruction credit.A research is designed as normative legal research in order to respond those problems byusing 2 types of approaches that consists of: The Statue Approach and The Legal ContentAnalitical Approach. The legal materials analyzed herein are primary legal material andsecondary legal material, arranged descriptively and systematically.Research shows that it is possible for the high-rise developer to change the building planprovided that before making any changes on the building plan, it must inform such changes tothe Association of High-Rise Residents and also has received approval from the Association ofHigh-Rise Residents, especially if such changes result in changes of the high-rise comparisonvalue. High-rise and high-rise unit can also be used as debt security through Mortgage/FiduciaryInstitution, which allows the developer to pledge the high-rise for construction credit, in whichthe high-rise unit that has been fully paid by its owner can be released from the credit security ofhigh-rise construction, thus the high-rise owner may then transfer their high-rise unit for creditsecurity of apartment ownership (KPA) as well as other financing credit security.